2020
DOI: 10.1017/s0007114520002007
|View full text |Cite
|
Sign up to set email alerts
|

Dried fruit consumption and cardiometabolic health: a randomised crossover trial

Abstract: Fruit intake is associated with lower risk of cardiometabolic diseases. However, effects of dried fruits on cardiometabolic health are not well researched. We investigated the effect of daily dried fruit consumption compared with a carbohydrate-rich snack on cardiometabolic disease risk factors in adults with increased cardiometabolic risk. A two-period randomised crossover trial was conducted in adults (n 55) with elevated BMI and at least one additional risk factor for cardiometabolic disease to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…Some studies have reported that raisin intake can reduce CVD risk factors such as plasma lipids, inflammatory cytokine levels, postprandial glucose levels, and systolic blood pressure ( 8 , 9 ). However, a recent study showed that dried fruit consumption did not improve cardiometabolic risk factors ( 11 ). Therefore, whether dried fruit intake can actually decrease CVD risk is inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported that raisin intake can reduce CVD risk factors such as plasma lipids, inflammatory cytokine levels, postprandial glucose levels, and systolic blood pressure ( 8 , 9 ). However, a recent study showed that dried fruit consumption did not improve cardiometabolic risk factors ( 11 ). Therefore, whether dried fruit intake can actually decrease CVD risk is inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dried fruits and nuts have been reported to help promote cardiometabolic health ( 10 ). Nonetheless, Sullivan VK found that dried fruit consumption did not reduce cardiometabolic risk factors ( 11 ). Therefore, these controversial findings highlight the need for further research to determine the causal relationship between dried fruit intake and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, most observational studies on the relationship between diet and cancer do not distinguish between dried fruit and raw fruit or do not mention the impact of dried fruit on cancer. Dietary guidelines in many countries also encourage people to choose non-juice-form fruits as much as possible, including dried fruit ( 16 ). Dried fruit is a stable form of fruit that remains fresh through drying technology; however, it mainly appears in the human diet as a snack, accounting for a relatively small proportion.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence from human intervention studies for cancer prevention by dried fruit consumption is very limited. Thus far, human intervention studies with dried fruits have focused on cardiometabolic health or other chronic diseases [ 42 , 43 , 44 ]. Some evidence is available for the function of high-value, freeze-dried berry products in healthy individuals and those with colorectal, oral, and prostate cancers [ 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Dried Fruits and Cancermentioning
confidence: 99%